Liposomes techniques of aerosolization for the treatment of obstructive, restrictive and infectious pulmonary diseases: a review (Research, Society and Development, 2023)
The current treatment of lung diseases, such as tuberculosis, chronic obstructive pulmonary disease (COPD), asthma, cancer and SARS-CoV-2, presents problems related to drug administration. Thus, nanotechnology, an innovative method that stands out in recent years, especially in nanomedicine, due to the development of materials on the nanometer scale (1-1000 nm). Among the various nanosystems, liposomes for their physicochemical properties, which make them a technology of interest to encapsulate hydrophilic or hydrophobic drugs, in addition to enabling controlled drug release. These techniques employed using an inhalation route have been considered as an alternative to deliver drugs encapsulated in site-specific liposomes. For this purpose, the literature describes several liposome aerosolization techniques in order to optimize an aerosolization system. The objective of this research was to carry out a bibliographic survey of the use of liposomes in the treatment of lung diseases as well as patents related to liposomes in aerosol dosage form. According to articles searched in Science Direct, Springer Nature, National Library of Medicine (PubMed) and Scientific Electronic Library Online (SCIELO) databases on the most used techniques such as Spray Drying, Spray Freeze Drying and Freeze Drying, specifically spray-drying is described in the literature as the solution base as the one that favors obtaining vesicles with low density, good fluidity and good dispersibility. In short, it was found that, linked to the use of spray-drying and nanotechnology, the inhalation route is a promising route for the administration of drugs aimed at the  of lung diseases.